GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI DALAM MEMPENGARUHI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI SEKRETARIAT DPRD SUMBAWA - Mawarhira; Fendy Maradita (Publika Citra Media, 2026)
This study aims to analyze the influence of leadership style, organizational culture, and organizational commitment on Organizational Citizenship Behavior (OCB) among employees of the Sumbawa DPRD Secretariat. This study uses a quantitative approach with a survey method. The population in this study were all 63 employees of the Sumbawa DPRD Secretariat, with the sampling technique using saturated sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of the SPSS program. The results of this study indicate that OCB behavior among employees of the Sumbawa DPRD Secretariat is not influenced by a single individual factor, but rather is formed through the interaction of various organizational factors. Therefore, improving OCB requires an integrated approach to managing leadership, organizational culture, and employee commitment.